X-ray evaluation of dislocation density in ODS-Eurofer steel - Renzetti, R. A. (2012)
The dislocation density of ferritic-martensitic oxide dispersion strengthened ODS-Eurofer steel was evaluated by using the modified Williamson-Hall method (peak broadening analysis). Measurements were performed in several metallurgical conditions (ferritic and martensitic structures). The monochromatic X-ray radiation was provided by a synchrotron source. The results match qualitatively with those provided by Vickers microhardness measurements and metallographic inspection using transmission electron microscopy.